Teachers’ Perceptions on Multiple Intelligences-Based Learning Strategies - Rahmawati, Puji; Wijayanto, Sukma (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aims to identify teacher perception toward Multiple Intelligences learning application in primary school. The descriptive qualitative was used as the research method. The data were collected by means of interviewing and documentation. The informants of this research were 5 (five) teachers of SD Muhammadiyah Inovatif Mertoyudan which were selected through purposive sampling. The data were inspected using triangulation method and source triangulation. The data analysis were conducted using qualitative data analysis which consisted of four steps: data collection, data reduction, data presentation, and data verification or conclusion. The research result indicated that teachers had various perceptions toward the appplication of Multiple Intelligences-based learning depended on the class level taught and the students' characteristics based on linguistic verbal, mathematical logical, visual spatial, kinesthetic, musical, interpersonal, intrapersonal, naturalist and existential intelligence.